DIVERSIFICAÇÃO E SEGURANÇA DA MATRIZ ELÉTRICA BRASILEIRA BASEADA EM RECURSOS RENOVÁVEIS EM FUNÇÃO DE CUSTOS E DEMANDA - Morila, Thiago Senatore (2021)
Electric energy is a common good necessary for the development of society, as all technology depends on its use. In this context, two important parameters allow analyzing the electric power generation sector: safety and diversity. Safety measures the syst